The Role of the Principal as a Supervisor and Motivator in Improving Teacher’s Performance at SD Negeri 123 Palembang - Fatimah, Raden Ayu; Emmawatie, Emmawatie; Ahmad, Syarwani (Yayasan Sembilan Pemuda Indonesia, 2023)
This study intends to describe and analyze three things: (1) teacher performance; (2) the principal’s supervision and motivation towards teachers; and (3) elements that encourage the supervision and motivation of school principals in improving teacher performance. The creation of a qualitative descriptive analysis strategy model and/or a qualitative verification analysis strategy model is a qualitative component of this study. At SD Negeri 123, Sukarame District, Palembang, this research was conducted with principals, 10 teachers and supervisors as respondents. Observations, interviews, and documentation are used as data collection methods. By using triangulation techniques, data analysis. From the research results it is known that the Principal of Public Elementary School (SD) 123, Sukarame District, Palembang has done a good job in motivating and supervising the teachers there. encouraging teachers, improving teacher performance, recognizing teacher abilities, and understanding.